Glutamate cycling may drive organic anion transport on the basal membrane of human placental syncytiotrophoblast. (9th September 2015) - Lofthouse, Emma M.; Brooks, Suzanne; Cleal, Jane K.; Hanson, Mark A.; Poore, Kirsten R.; O'Kelly, Ita M.; Lewis, Rohan M.
Abstract : Key points: The placenta removes waste products, drugs and environmental toxins from the fetal circulation and two of the transport proteins responsible for this are OAT4 and OATP2B1 localised to the basal membrane of placental syncytiotrophoblast. We provide evidence that OAT4 and OATP2B1 mediate glutamate efflux when expressed in Xenopus oocytes and that in the perfused placenta, bromosulphothalein (an OAT4 and OATP2B1 substrate) stimulates glutamate efflux. Furthermore the efflux of glutamate can only be seen in the presence of aspartate, which will block glutamate reuptake by the placenta, consistent with cycling of glutamate across the basal membrane. We propose that glutamate efflux down its transmembrane gradient drives placental uptake via OAT4 and OATP2B1 from the fetal circulation and that reuptake of glutamate maintains this driving gradient. Abstract: The organic anion transporter OAT4 (SLC22A11) and organic anion transporting polypeptide OATP2B1 (SLCO2B1) are expressed in the basal membrane of the placental syncytiotrophoblast. These transporters mediate exchange whereby uptake of one organic anion is coupled to efflux of a counter‐ion. In placenta, these exchangers mediate placental uptake of substrates for oestrogen synthesis as well as clearing waste products and xenobiotics from the fetal circulation. However, the identity of the counter‐ion driving this transport in the placenta, and in other tissues, is unclear. While glutamate is not a known OAT4 or OATP2B1 substrate, we propose that its high intracellular concentration has the potential to drive accumulation of substrates from the fetal circulation. In the isolated perfused placenta, glutamate exchange was observed between the placenta and the fetal circulation. This exchange could not be explained by known glutamate exchangers. However, glutamate efflux was trans‐stimulated by an OAT4 and OATP2B1 substrate (bromosulphothalein). Exchange of glutamate for bromosulphothalein was only observed when glutamate reuptake was inhibited (by addition of aspartate). To determine if OAT4 and/or OATP2B1 mediate glutamate exchange, uptake and efflux of glutamate were investigated in Xenopus laevis oocytes. Our data demonstrate that in Xenopus oocytes expressing either OAT4 or OATP2B1 efflux of intracellular [ 14 C]glutamate could be stimulated by conditions including extracellular glutamate (OAT4), estrone‐sulphate and bromosulphothalein (both OAT4 and OATP2B1) or pravastatin (OATP2B1). Cycling of glutamate across the placenta involving efflux via OAT4 and OATP2B1 and subsequent reuptake will drive placental uptake of organic anions from the fetal circulation. Abstract :